2020
DOI: 10.32942/osf.io/xp5km
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges and opportunities of species distribution modelling of terrestrial arthropod predators

Abstract: Species distribution models (SDMs) are emerging as essential tools in the equipment of many ecologists; they are useful in exploring species distributions in space and time and in answering an assortment of questions related to historical biogeography, climate change biology and conservation biology. Given that arthropod distributions are strongly influenced by microclimatic conditions and microhabitat structure, they should be an ideal candidate group for SDM research, especially generalist predators because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 141 publications
0
8
0
Order By: Relevance
“…These examples collectively illustrate the complex interplay of the three diversity metrics in natural ecosystems. Therefore, predicting how changes in those metrics might affect long term ecosystem function and stability is challenging and not only requires highquality data, but also mechanistic modelling 45 .…”
Section: Discussionmentioning
confidence: 99%
“…These examples collectively illustrate the complex interplay of the three diversity metrics in natural ecosystems. Therefore, predicting how changes in those metrics might affect long term ecosystem function and stability is challenging and not only requires highquality data, but also mechanistic modelling 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a growing interest in the application of ENMs to odonates ( Patten et al 2015 , Pires et al 2018 , Rodríguez-Tapia et al 2020 ). But, multispecies ENMs are still rare for odonates ( Collins and McIntyre 2015 ) and represent a very low portion of arthropod ENMs published ( Mammola et al 2021 ). For instance, Hickling et al (2005) found an average northward range shift of 74 km between 1960 and 1995 for 37 nonmigratory British odonates with an increase in range size for all but two species.…”
mentioning
confidence: 99%
“…Therefore, further research about ecology, physiology, and behaviour can benefit our knowledge about these freshwater insects and favour the design of efficient and effective conservation strategies. Further investigations based on mechanistic models (Chichorro et al ., 2022) or high-resolution physiological and dispersal traits (Buckley & Kingsolver, 2012; Mammola et al ., 2021b) could be useful to better identify key traits associated with climate-induced species range shifts and potentially even extinction risk. Our results might be substantially improved by including into the models traits directly linked with the dispersal ability (e.g., GPS-tracking, flight muscle mass, wing loading and shape) as well as traits and distribution of the larval stages, since most of the life of these insects is spent underwater [e.g., in Anax imperator (Leach, 1815) the life span is two years in larvae and eight to nine weeks in adults (Corbet, 1957)].…”
Section: Discussionmentioning
confidence: 99%
“…To model species distribution, we used Species Distribution Models (SDMs), mainstream analytical tools in ecological and biogeographical research (Peterson et al ., 2011; Franklin, 2010; Guisan and Thuiller, 2005), including to predict arthropod distributions (Mammola et al ., 2021b). In short, distribution modelling refers to the practice of using an algorithm to infer a relationship between the occurrences for a given species (e.g., georeferenced points) and environmental predictors (e.g., climatic variables, topographic parameters, habitat type), forecasting its potential distribution in space and/or time.…”
Section: Methodsmentioning
confidence: 99%